HTML5 and JavaScript projects : build on your basic knowledge of HTML5 and JavaScript to create substantial HTML5 applications - Meyer, Jeanine (Apress, 2018)
Build on your basic knowledge of HTML5 and JavaScript to create substantial HTML5 applications. Through the many interesting projects you can create in this book, you'll develop HTML5 skills for future projects, and extend the core skills you may have learned with its companion book, The Essential Guide to HTML5 . HTML5 and JavaScript Projects is fully updated as a second edition and covers important programming techniques and HTML, CSS, and JavaScript features to help you build projects with images, animation, video, audio and line drawings. You'll learn how to build games, quizzes and other interactive projects; incorporate the use of the Google Maps API and localStorage; and address the challenges of Responsive Design and Accessibility. Each project starts out with a description of the example's operation, often with full-color illustrations. You'll then review the HTML5 and JavaScript concepts that relate to the project followed by a step-by-step explanation of the programming used. Tables are used to show the relationship of functions and provide comments for each line of code so that you can easily apply the techniques to your own HTML5 projects.​ What You'll Learn Enhance your HTML5 and JavaScript programming skills. Poduce applications combining Canvas drawings, photos, and videos Incorporate Google Maps and geolocation into your projects Build applications requiring persistent data, storing the information locally or on a database on the server Who This Book Is For Developers who have some knowledge of programming and want to build more substantial applications by combining basic features and combining JavaScript with other technologies.